Branded content: relações entre jornalismo e publicidade - Povineli, Isabel (2020)
This project had as its research theme the Branded Content narrative used for advertising, a tool that has called the attention of the market and consumers by promoting an approximation between the advertising language and the journalistic language, hoping thereby to engage the consumer, to achieve relevance and consequently to reach results. It was sought through the theoretical basis to know the opinion of several authors about the transformations that are happening through which advertising is passing, the relevance of brands in the lives of consumers, until the re-signification of journalism, which also undergoes through transformations to become economically viable. From this analysis, the foundations of Branded Content as a hybrid language that can contribute to a new relationship between brands and consumers were stated. After learning the concepts, a Case Study and Content Analysis of the Jeep brand were presented, which used the Branded Content tool in its new print media campaign to position itself in a differentiated way, highlighting its causes and the attributes of the product. In order to do so, consideration has been given to the advertising and journalistic languages used in the advertisement pieces, showing that the hybridism of this combination is called Branded Content.